1999
DOI: 10.1103/physrevb.60.r8430
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound investigations of orbital quadrupolar ordering inUPd3

Abstract: For a high-quality single crystal of UPd 3 we present the relevant elastic constants and ultrasonic attenuation data. In addition to the magnetic phase transition at T 2 ϭ4.4Ϯ0.1 K and the quadrupolar transition at T 1 ϳ6.8 K, we find orbital ordering at T 0 ϭ7.6Ϯ0.1 K concomitant with a symmetry change from hexagonal to orthorhombic. A striking feature is the splitting of the phase transition at T 1 into a second-order transition at T ϩ1 ϭ6.9Ϯ0.05 K and a first-order transition at T Ϫ1 ϭ6.7Ϯ0.05 K. For the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Secondly, by subsequently improving the process of material production, handling and characterization an attempt is made to identify the intrinsic properties of the ''perfect'' compound [36][37][38][39][40][41][42][43]. For this, preferably single crystalline materials should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, by subsequently improving the process of material production, handling and characterization an attempt is made to identify the intrinsic properties of the ''perfect'' compound [36][37][38][39][40][41][42][43]. For this, preferably single crystalline materials should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies of elastic moduli and absorption of ultrasound in the vicinity of a phase transition are observed very often (see, for example, [12,13]). However, what we have observed in ZnSe:Ni could scarcely be explained only as the result of a phase transition.…”
Section: Discussionmentioning
confidence: 98%
“…A range of microscopic [5][6][7] and macroscopic [8][9][10] experimental studies of UPd 3 have shown clear evidence of four phase transitions at T 0 ¼ 7:8 K, T þ1 ¼ 6:9 K, T À1 ¼ 6:7 K and T 2 ¼ 4:4 K, which we have attributed to a succession of quadrupolar ordered phases. Whilst indirect evidence of quadrupolar order was deduced some years ago from PND measurements in a magnetic field [6], the first direct microscopic evidence for quadrupolar ordering was obtained by resonant X-ray diffraction studies [7].…”
Section: Introductionmentioning
confidence: 97%